Expression levels of some genes in the MAPK pathway (DUSP1, DUSP2, DUSP4, DUSP6 and DUSP10) in eyelid tumor tissue - Ozmen Esma; Tas Ayca; Akin Dilara Fatma; Erdogan Haydar; Silig Yavuz (Türk Biyokimya Dergisi)
To control mitogen-activated protein kinases (MAPK) signaling pathways involved in the onset and progression of cancer, dual specificity phosphatases (DUSPs/MKP) are essential. This study seeks to detect the correlation between eyelid tumors and the genes DUSPs, known for their influence on MAPK signaling pathways. Additionally, we aim to juxtapose our findings with analyses from various bioinformatics databases.